2017
DOI: 10.2147/jn.s120929
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal transplantation of olfactory ensheathing cells by lumbar puncture for thoracic spinal cord injury in mice

Abstract: *These authors contributed equally to this workObjectives: To investigate the distribution and function of olfactory ensheathing cells (OECs) following lumbar puncture (LP) transplantation in mouse spinal cord injury (SCI). Methods: OECs were transplanted by LP at level L3-5, 1 week after transected SCI at T8 vertebra. Mice were killed at 3, 21, and 56 days after LP transplantation, and the relative distribution of cells at T8 vertebra was quantitated. The injured spine was also tested by immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The safety of cell transplantation also needs to be evaluated by monitoring the viability, biodistribution, and trafficking of the transplanted cells. Previous studies have shown that intraspinal or intrathecal transplantation of OECs has positive results in the treatment of SCI 42 , 43 . However, these methods of transplantation carry some degree of risk for additional neurological damage to the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of cell transplantation also needs to be evaluated by monitoring the viability, biodistribution, and trafficking of the transplanted cells. Previous studies have shown that intraspinal or intrathecal transplantation of OECs has positive results in the treatment of SCI 42 , 43 . However, these methods of transplantation carry some degree of risk for additional neurological damage to the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The major challenge associated with cell-based therapy regarding SCI is to find the most cost-effective approaches to noninvasively deliver cells to the therapeutic targets. The current strategies for transplantation of olfactory bulb OECs include intraspinal injection 46 and intrathecal administration 47 . Although these methods are acceptable for scientific studies in animals, they are difficult to implement in clinical practice for treating human SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, nearly 20% of the cell transplantation-based clinical trials for SCI were conducted around the use of OECs. OECs have been proven safe for transplantation in animal spinal cord injury models and they have shown varying degrees of success at restoring sensory, motor, and autonomic functions following treatments in rodents [ 18 , 19 , 20 , 32 , 33 , 34 , 35 , 36 , 37 ], canine [ 15 ], and primate models [ 17 ]. Based on the evidence from pre-clinical studies, OECs are a promising, low-risk therapeutic candidate for clinical translation with a high chance of success.…”
Section: What To Translate To a Clinical Trial?mentioning
confidence: 99%